Pengaruh Pendapatan Asli Daerah dan Dana Alokasi Umum Terhadap Belanja Modal pada Provinsi di Indonesia - Rowena, Evin Framudita; Hanifa, Nurul (Independent: Journal of Economics, 2024)
Capital expenditure is a budget allocated to support economic development in enhancing public services and driving economic growth, supported by local revenue and general allocation funds. However, in its realization in Indonesian provinces, capital expenditure budgets have not been fully in line with the allocated ceiling. This research is conducted with the aim of determining the influence of the Local Revenue and General Allocation Fund on Capital Expenditure in Indonesia from 2018 to 2022. The method used is quantitative research with panel data regression testing. The results show that Local Revenue and General Allocation Fund simultaneously have a significant influence on capital expenditure. Partially, Local Revenue and General Allocation Fund each also have a significant positive influence on capital expenditure in Indonesian provinces.